Stress level amongst parents of Neonatal Intensive Care Unit (NICU) graduates vs parents of pediatric intensive care unit (picu) graduates in rural teaching hospital - A comparative study - Parthavi Patel; Prasad Muley; Maitray patel (Wolters Kluwer Medknow Publications, 2015)
Objective: To compare the stress amongst parents whose babies were admitted in NICU with that of the parents of children admitted in PICU Methods: Prospective study conducted at a tertiary level hospital with well equipped NICU and PICU. Eligible parent's (both mother and father) stress level was analyzed with the help of Parental Stress Scale (PSS). Results: Total 120 participants (mother and father) with 60 from each group were subjected to PSS. Mean score of fathers and mothers whose children were admitted to PICU had more stress as compared to those in NICU (p-value <0.001). Similarly stress was more in less educated (p-value<0.005) and low income group (p-value <0.01) parents. Conclusion: Our study concludes that guardians of children admitted to PICU have more Stress compared to that of neonates admitted in NICU and stress is negatively related with their educational qualification, income and number of children.